Healing process in anastomosis of homologous venous grafts preserved in glutaraldehyde implanted aorta of rabbits - Moura, R. [UNESP] (2003)
Aim. Autologous vein (AV) is sometimes not suitable or present for a vascular restoration. Homologous vein preserved in glutaraldehyde may be an alternative to AV, but little is yet known about this graft and its healing process after implantation in arteries. The purpose of this study was to compare the initial healing process of glutaraldehyde-tanned homologous venous grafts (group 1) with fresh autologous venous grafts (group 2), at 4 or 15 days. Methods. Forty Norfolk rabbits were allocated in 2 groups of 20 animals each. The grafts was interposed in the infrarenal aorta of the rabbit. Anastomotic tensile strength (TS), hydroxyproline (HP) determination, and histology (HA) were performed. Results. TS increased in both groups, from the 4th to 15th day, (p<0.01) in both proximal (G1: from 364.5±98.3 g to 491.8±107.3 g; G2: from 366.26±85.15 g to 518.46±82.79 g) and distal anastomosis (G1: from 363.53±96.26 g to 507.32±9 1.01 g; G2: from 352.30±102.41 g to 528.67±48.58 g), with no difference between the groups. HP did not change (p>0.10) in this same period and was similar in both groups, in the proximal (G1: from 677.99±153.98 μg/100 mg to 914.92±459.83 μg/100 mg; G2: from 668.65±170.28 μg/100 mg to 669.46±319.80 μug/100 mg) as well as in the distal anastomosis (G1: from 740.07±213.53 μg/100 mg to 923.52±270.57 μg/100 mg; G2: from 737.66±266.76 μg/100 mg to 707.68±171.25 μg/100 mg). Initial inflammatory and reparative features of the anastomosis were similar in both groups. Conclusion. We can conclude that the healing process of the glutaraldehyde-tanned homologous vein graft was similar to that of the fresh autologous venous graft.